Le leadership des chefs d’établissement : un exercice en tensions et balances - Jean-Marie De Ketele (Recherches en Éducation)
Based on the analysis of a work undertaken by French and English researchers, this concluding chapter draws the findings together in a model of distributed learning. This model comprises eight dimensions that are compared and contrasted. It reveals four founding principles of leadership that the author attempts to characterize and symbolize metaphorically. The findings pave the way for more extensive debate and further research.